2017
DOI: 10.1039/c7ra01901g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of g-C3N4 nanosheet modified SnO2 composites with improved performance for ethanol gas sensing

Abstract: Considering the facile effective synthesis approach and high gas sensing performance for ethanol vapor, the g-C3N4 nanosheet modified SnO2 composite will be an ideal candidate for ethanol gas sensor applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Wang et al synthesized holey reduced graphene oxide nanosheets with high sensor response and reversible sensing for NH 3 detection [22]. Cao et al improved sensing properties through g-C 3 N 4 nanosheets decorated SnO 2 composites toward ethanol gas [23]. Chen et al reported that Co 3 O 4 -rGO nanoparticles showed a good response and recovery to methanol [24].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al synthesized holey reduced graphene oxide nanosheets with high sensor response and reversible sensing for NH 3 detection [22]. Cao et al improved sensing properties through g-C 3 N 4 nanosheets decorated SnO 2 composites toward ethanol gas [23]. Chen et al reported that Co 3 O 4 -rGO nanoparticles showed a good response and recovery to methanol [24].…”
Section: Introductionmentioning
confidence: 99%
“…9d shows three different peaks centered around 397.8 eV, 399.7 eV and 403.5 eV, which are derived from the sp 2 -hybridized nitrogen of N-C]N, the tertiary nitrogen of N-(C) 3 , and the p-excitation in the C-N groups, respectively. [49][50][51] In the terms of N1s in the hybrid S 15 , the corresponding peaks shi to 398.0 eV, 400.2 eV and 403.6 eV, which may be attributed to the interaction role of SCN and diatomite. Photocatalytic degradation of model pollutants over different photocatalysts were evaluated under visible light irradiation (l > 400 nm).…”
Section: Resultsmentioning
confidence: 94%
“…4(a)) indicates that MLTPS consists of Sn and O elements. 31 As shown in Fig. 4(b), the peaks in the Sn 3d spectrum located at 486.63 eV and 495.03 eV originate from the Sn 3d 5/2 and Sn 3d 3/2 core level states, respectively.…”
Section: Characterization Of Mltpsmentioning
confidence: 87%